1978
DOI: 10.1152/jappl.1978.45.5.778
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bronchodilatation in normal subjects: beta agonist versus atropine

Abstract: Bronchodilatation was produced in normal subjects by the inhalation of a parasympatholytic agent (atropine) and the response was compared to that occurring after the inhalation of a beta-adrenergic agent (isoetharine). Doses were chosen that resulted in equivalent increases in specific airway conductance (78 +/- 9% for atropine; 88 +/- 21% for isoetharine). Anatomic dead space and volume at the onset of the terminal nitrogen rise (closing volume) were measured before and after each agent. Although there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 0 publications
3
27
1
Order By: Relevance
“…From the analysis of maximal expiratory flow-volume curves with inspired gases of different densities, Ingram et al (1977) suggested that in normal subjects the predominant sites of atropine aerosol activity are the central airways and sites of isoproterenol are the peripheral airways. Later, using the concept that changes in anatomic dead space reflect changes in central airway dimension, Hensley et al (1978) reached the same conclusion.…”
Section: Treatment Of Peripheral Airway Hyperreactivitymentioning
confidence: 76%
See 1 more Smart Citation
“…From the analysis of maximal expiratory flow-volume curves with inspired gases of different densities, Ingram et al (1977) suggested that in normal subjects the predominant sites of atropine aerosol activity are the central airways and sites of isoproterenol are the peripheral airways. Later, using the concept that changes in anatomic dead space reflect changes in central airway dimension, Hensley et al (1978) reached the same conclusion.…”
Section: Treatment Of Peripheral Airway Hyperreactivitymentioning
confidence: 76%
“…Therefore, in contrast to atropine, there is general agreement that fi adrenergic agents exert their bronchodilating effects on both the central and peripheral airways (Barnes et al 1983). In normal subjects, large airway dilation is produced by atropine, whereas small airway dilation is produced by fl-agonist (Hensley et al 1978). McFadden et al (1977) reported that postexertional asthma with large airway constriction could be abolished by pretreatment with an anticholinergic agent, whereas small airway constriction could be abolished by pretreatment with disodium cromoglycate.…”
Section: Treatment Of Peripheral Airway Hyperreactivitymentioning
confidence: 99%
“…Contrasting with the adrenergic agents, the bronchodilator effects of anticholinergic agents may favor the large airways rather than the small airways. 25 Regardless of the site of action of bronchodilators, as in other lung diseases, 26 some patients with LAM may respond more favorably to one or the other category of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have included measuring anatomical dead space as an indicator of central airway changes, [26] generating maximal expiratory flow-volume curves with inspired gases of different densities [27,28] and sensing the lateral pressure of the airway using a catheter-tipped micro manometer. [29] Although these studies were theoretically sound, they could not determine bronchodilatory heterogeneity of in the lung because they are all based on the assumption that lung activity is homogeneous and so overall physiological parameters were measured.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Although these studies were theoretically sound, they could not determine bronchodilatory heterogeneity of in the lung because they are all based on the assumption that lung activity is homogeneous and so overall physiological parameters were measured. Most of these studies agreed that inhaled anticholinergic agents act mainly on the large central airways in normal individuals as well as in patients with bronchial asthma, [26,28,30] although some disagreed. [27,31] Since resting vagal tone is thought to be maintained under normal circumstances throughout the bronchial tree,[30] the exact site of bronchodilation over the whole lung remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%